2022
DOI: 10.1016/j.heliyon.2021.e08698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of heat stress on cognitive performance of petrochemical workers: A field study

Abstract: Introduction: Heat stress disrupts blood hormones and reduces workers' cognitive performance. To further shed light on the dysfunction of heat stress, the present study aimed to evaluate its effect on cognitive performance of petrochemical workers. Materials and methods: This descriptive-analytical cross-sectional study was conducted in 2020 in one of the Iranian petrochemical companies. Participants were divided into 2 case groups and 1 control group. They worked 12 h and their shift entialed one week working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The mean ( ± SD) age and work experience of workers were 33.87 (5.95) and 9.71 (4.90) years, respectively. Additionally, the minimum and maximum age of the workers were 23 and 50 years, respectively, and the median of the equivalent sound level was equal to 87 (7). Table 1 provides the results of demographic variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean ( ± SD) age and work experience of workers were 33.87 (5.95) and 9.71 (4.90) years, respectively. Additionally, the minimum and maximum age of the workers were 23 and 50 years, respectively, and the median of the equivalent sound level was equal to 87 (7). Table 1 provides the results of demographic variables.…”
Section: Resultsmentioning
confidence: 99%
“…The results of various studies show that noise exposure and noise annoyance reduce the level of attention and concentration, and thus increase the level of errors (5,6). The slightest delay in the reaction of people in sensitive jobs can lead to increased accidents and irreparable risks (7).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that working in an environment of excessive heat in a variety of jobs was associated with an increased risk of cognitive impairments ( 34 ). The MetSyn group in the present study showed impaired working memory compared with the non-MetSyn group.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research across contexts has focused on the cognitive implications of these strategies [ 45 ]. This is despite increased exposure as to the importance of optimising CP for human performance across contexts [ 46 , 47 ], and the known implications of heat strain for the execution of fundamental cognitive skills [ 20 , 48 ]. Therefore, there is a need to rigorously synthesise the evidence base as to how heat preparation and alleviation strategies, traditionally adopted for the facilitation of physical performance, affect CP across occupational, educational, and athletic contexts.…”
Section: Introductionmentioning
confidence: 99%